2020
DOI: 10.3390/vaccines8010050
|View full text |Cite
|
Sign up to set email alerts
|

Infections, Vaccines and Autoimmunity: A Multiple Sclerosis Perspective

Abstract: Background: Multiple sclerosis (MS) is a chronic neuroinflammatory and neurodegenerative disease that is associated with multiple environmental factors. Among suspected susceptibility events, studies have questioned the potential role of overt viral and bacterial infections, including the Epstein Bar virus (EBV) and human endogenous retroviruses (HERV). Furthermore, the fast development of immunomodulatory therapies further questions the efficacy of the standard immunization policies in MS patients. Topics rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 142 publications
(263 reference statements)
0
26
0
3
Order By: Relevance
“…Microbial infections can act as triggers for inducing autoimmunity and clinical disease manifestations in genetically predisposed individuals [32][33][34][35]. Studies have suggested a robust relationship between viral infections and exacerbations of MS [36][37][38][39][40][41][42][43][44][45]. Based on the aforementioned studies, COVID-19 carries additional reasons for concern because of taking immunosuppressive therapies in MS patients [47,48] and also the fact that viral infections may contribute to MS exacerbation and relapses as an environmental factor [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Microbial infections can act as triggers for inducing autoimmunity and clinical disease manifestations in genetically predisposed individuals [32][33][34][35]. Studies have suggested a robust relationship between viral infections and exacerbations of MS [36][37][38][39][40][41][42][43][44][45]. Based on the aforementioned studies, COVID-19 carries additional reasons for concern because of taking immunosuppressive therapies in MS patients [47,48] and also the fact that viral infections may contribute to MS exacerbation and relapses as an environmental factor [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…VLPs are the most widely applied nanosystem for antiviral vaccines. Currently available HPV vaccines, such as Gardasil, Gardasil 9, and Cervarix, which effectively protect women from HPV infection, are all nano-based VLP vaccines [ 81 ]. A VLP vaccine against HEV, Hecolin, is also commercially available [ 82 ].…”
Section: Nano-based Vaccinesmentioning
confidence: 99%
“…For similarity with what has been shown for infections, it was thought that vaccines could also lead to demyelination. In some cases, a strict temporal relationship between vaccine administration and the development of CNS demyelinating syndromes has been reported, favoring the hypothesis that vaccine administration, despite being able to ensure protection against some infections, could be deleterious and cause clinical problems sometimes even more severe than the prevented disease (15). Most of the reported cases concerned hepatitis B vaccine (HBV) and human papillomavirus vaccine (HPV).…”
Section: Vaccines and Central Nervous System (Cns) Demyelinating Syndmentioning
confidence: 99%